Association among smoking, depression, and anxiety: findings from a representative sample of Korean adolescents - Haewon Byeon (PeerJ, 2015)
This study investigated the relationship between smoking and depression and anxiety using data from a nationwide survey representing Korean adolescents. Subjects were 6,489 adolescents in middle and high school (age 13–18) who had participated in the 2011 Korean Study of Promotion Policies on Children and Adolescents—Mental Health (KSPCAM). Daily smoking number of times for current smokers was classified as 1–2 times, 2–4 times and over 5 times. The odds ratio for the statistical test was presented using hierarchical logistic regression. When adjusted for covariates (gender, age, household economy, type of residing city, type of school, school record, satisfaction with school life, subjective health status, satisfaction with relationship with parents, and drinking experience), smokers more significantly likely to have depression (OR = 1.27, 95% CI [1.02–1.57]), and anxiety (OR = 1.49, 95% CI [1.14–1.96]) than non-smokers (p < 0.05). In addition, adolescents who smoke more than 5 cigarettes a day were 1.5 times more likely to have depression (OR = 1.48, 95% CI [1.13–1.92]) and anxiety (OR = 1.49, 95% CI [1.07–2.08]) than those who do not smoke. Smoking in adolescence was found to be significantly related with depression and anxiety. To promote the mental health of adolescents, effective smoking cessation programs are required.